Fear below [videorecording (DVD)] - Northfield, Blake; Favelle, Michael; Holmes, Matthew; Moss, Gregory; Corfield, Hermione, 1993-; Ryan, Jake (Actor); McConville, Josh; Nayinggul, Jacob Junior (Well Go USA Entertainment, 2025)
After crashing their van of stolen gold into a river, a group of ruthless gangsters hire a team of down-on-their-luck divers to retrieve their loot. In an attempt to reach the gold, the divers soon find themselves in the company of a vicious bull shark, but the dangers in the water are only a fraction of the dangers that wait for them above.